Report on Public Administration by A. D. Gorwala - Planning Commission (Planning Commission, 1951)
This report examines the nature, condition, and challenges of public administration in India, emphasising that administration is both a science and an art requiring continuous evaluation to ensure it effectively serves public welfare, particularly in the context of expanding developmental responsibilities. It highlights the intrinsic connection between administrative efficiency and the quality of governance, noting that the effectiveness of administrative machinery is deeply influenced by political leadership, institutional structures, and societal values within a democratic framework. The analysis reveals signs of deterioration in administrative performance, including declining efficiency, inadequate coordination, and reduced quality of personnel, alongside widespread public dissatisfaction driven by economic hardships, delays in decision-making, lack of transparency, and perceived corruption among officials and political leaders. The report underscores that administrative shortcomings are compounded by broader issues such as rising cost of living, scarcity of essential goods, and weakened public trust in institutions. A significant portion of the discussion focuses on moral and ethical decline, attributing it partly to wartime economic distortions and the superficial internalisation of high political ideals during the independence movement, resulting in weakened discipline and integrity in public life. It argues that effective planning and national development depend fundamentally on a clean, efficient, and impartial administrative system supported by strong moral foundations, disciplined governance, and a renewed commitment to public service, thereby stressing the urgent need for both structural reforms and ethical regeneration to strengthen the administrative framework.
Planning Commission, Government of India
Planning Commission, Government of India
Keywords: Public Administration, Administrative Efficiency, Democratic Governance, Moral Decline, Government Machinery, Public Dissatisfaction, Corruption, Policy Implementation, Economic Conditions, Administrative Reform, Political System, National Development